Computational implementation of bounding surface model and its verification through cavity benchmark problems - Chen, Shengli; Abousleiman, Younane; Muraleetharan, Kanthasamy K. (International journal for numerical and analytical methods in geomechanics, 2022)
This paper develops an implicit integration algorithm for a general form of the bounding surface model, using the return mapping approach (elastic predictor‐plastic corrector), to obtain the updated stresses for given strain increments. The formulation of the constitutive integration requires the derivation of a supplementary differential equation to describe the evolution of a key variable, that is, the ratio between the image stress and the current stress quantities. The integration algorithm for the bounding surface model is implemented into the finite element analysis commercial program, ABAQUS, through the material interface of UMAT (user defined material subroutine), and then used for the analysis of cavity contraction (wellbore drilling/tunnel excavation) boundary value problems. The predictions from the ABAQUS simulations are found to be in excellent agreement with the analytical solutions, thus demonstrating the validity and accuracy of the proposed integration scheme.